Improving Class III Mathematics Learning Outcomes Student Teams Achievement Division (STAD) Learning Model - Perwitasari, Novia Madyas (Universitas Sebelas Maret, 2022)
This study aims to improve the learning outcomes of students in the Mathematics course in grade III elementary schools with the Student Teams Achievement Division (STAD) learning model. The research conducted was Classroom Action Research (PTK) in two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out pre-test and post-test to determine the progress of students. In the pre-cycle, students who completed after carrying out the post test were 41%. In cycle I, students who completed after carrying out the post test were 58%. In cycle II, students who passed after carrying out the post test were 91%. These results indicate that the Student Teams Achievement Division (STAD) learning model can improve student learning outcomes, especially Mathematics Class III at SD N 01 Plosorejo.